The Role of RASSF1A Methylation in Cancer. Issue 1 (6th June 2013) - Hesson, Luke B.; Cooper, Wendy N.; Latif, Farida
Abstract : Tumour suppressor gene inactivation is critical to the pathogenesis of cancers; such loss of function may be mediated by irreversible processes such as gene deletion or mutation. Alternatively tumour suppressor genes may be inactivated via epigenetic processes a reversible mechanism that promises to be more amenable to treatment by therapeutic agents. The CpG dinucleotide is under-represented in the genome, but it is found in clusters within the promoters of some genes, and methylation of these CpG islands play a critical role in the control of gene expression. Inhibitors of the DNA methyltransferases DNMT1 and DNMT3b have been used in a clinical setting, these nucleotide analogues lack specificity but the side effects of low dose treatments were minimal and in 2004 Vidaza (5-azacitidine) was licensed for use in myelodysplastic syndrome. Methylation inhibitors are also entering trials in conjunction with another class of epigenetic modifiers, the histone deacetylase inhibitors and this epigenetic double bullet offers hope of improved treatment regimes. Recently there has been a plethora of reports demonstrating epigenetic inactivation of genes that play important roles in development of cancer, including Ras-association domain family of genes. Epigenetic inactivation of RASSF1A (Ras-association domain family 1, isoform A) is one of the most common molecular changes in cancer. Hypermethylation of the RASSF1A promoter CpG island silences expression of the gene in many cancers including lung, breast, prostate, glioma, neuroblastoma and kidney cancer. Several recent studies have illustrated the diagnostic and prognostic potential of RASSF1A methylation. This presents RASSF1A methylation as an attractive biomarker for early cancer detection which, for most cancers, results in improved clinical outcome. DNA methylation analysis is applicable to a range of body fluids including serum, urine, bronchioalveolar lavage and sputum. The ease with which these body fluids can be acquired negates the need for invasive procedures to obtain biopsy material. This review will discuss the feasibility of using RASSF1A methylation as a diagnostic and prognostic marker in cancer management.